Investigating potential future changes in surface water flooding hazard and impact. Issue 1 (12th September 2019) - Rudd, Alison C.; Kay, Alison L.; Wells, Steven C.; Aldridge, Timothy; Cole, Steven J.; Kendon, Elizabeth J.; Stewart, Elizabeth J.
Abstract: Surface water flooding (SWF) is a recurrent hazard that affects lives and livelihoods. Climate change is projected to change the frequency of extreme rainfall events that can lead to SWF. Increasingly, data from Regional Climate Models (RCMs) are being used to investigate the potential water‐related impacts of climate change; such assessments often focus on broad‐scale fluvial flooding and the use of coarse resolution (>12 km) RCMs. However, high‐resolution (<4 km) convection‐permitting RCMs are now becoming available that allow impact assessments of more localised SWF to be made. At the same time, there has been an increasing demand for more robust and timely real‐time forecast and alert information on SWF. In the UK, a real‐time SWF Hazard Impact Model framework has been developed. The system uses 1‐km gridded surface runoff estimates from a hydrological model to simulate the SWF hazard. These are linked to detailed inundation model outputs through an Impact Library to assess impacts on property, people, transport, and infrastructure for four severity levels. Here, a set of high‐resolution (1.5 km and 12 km) RCM data has been used as input to a grid‐based hydrological model over southern Britain to simulate Current (1996–2009) and Future ( 2100s; RCP8.5) surface runoff. Counts of threshold‐exceedance for surface runoff and precipitation (at 1‐, 3‐ and 6‐hr durations) are analysed. Results show that the percentage increases in surface runoff extremes, are less than those of precipitation extremes. The higher‐resolution RCM simulates the largest percentage increases, which occur in winter, and the winter exceedance counts are greater than summer exceedance counts. For property impacts, the largest percentage increases are also in winter; however, it is the 12‐km RCM output that leads to the largest percentage increase in impacts. The added‐value of high‐resolution climate model data for hydrological modelling is from capturing the more intense convective storms in surface runoff estimates.